Kajian Konstruksi Model Peredam Gelombang Dengan Menggunakan Mangrove Di Pesisir Lateri - Kota Ambon - Sonja T. A. Lekatompessy (Industrial Engineering Study Program, Pattimura University, 2010)
The wave reflection in coastal protection structure is important. Wave reflection represented the parameter to measure the ability of a structure to reflect wave. The accurate structure planning is needed to find the reduction of wave reflection coefficient. The aim of this research is to know the relation between wave reflection coefficient (Kr) that happened with strongly on the density of the mangrove. This research present result of attempt physic model of measurement wave reflection on 2 mangrove model with variation mangrove density. Regular waves having various wave periods (T) between 5 sec up to 8 sec, and various wave heights (H) between 0.15 m up to 0.4 m. The attempt result is concluded by the structure mangrove tend to reduce the wave reflection at the examination of short wave period on high of big wave at every attempt.